Bryophytes from anthropic areas of the State Park of Serra do Mar, Núcleo Picinguaba, Ubatuba, São Paulo State, Brazil - Visnadi, Sandra Regina (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
The human actions have increased the occurrence of bryophytes in different kinds of environments and substrates. The paper list 110 species for the bryoflora from anthropic areas of the State Park of Serra do Mar, Núcleo Picinguaba in Ubatuba, São Paulo State, Brazil. The material was collected in natural and artificial substrates and it totalizes 172 exsiccatae, which are deposited in the Herbarium Maria Eneyda Pacheco Kauffmann Fidalgo (SP) and Herbarium Rioclarense (HRCB). The liverworts on soil and rocks predominate in the bryoflora, which species are mostly generalists and presents mat life form. The studied bryoflora is similar to those occurring in the restinga and the slope Atlantic rainforest. The study area is limited by the other areas, where these two latter ecosystems are preserved in the State Park of Serra do Mar, which is an Integral Protection Unit of the paulista nature. Few species are restricted to the anthropic areas, not occurring in other ecosystems of Picinguaba, and among these even fewer was already related to the human occupation. Most of the listed species shows a worldwide distribution, occurring also in all states of Brazil.